Understanding integrated service delivery: a scoping review of models for noncommunicable disease and mental health interventions in low-and-middle income countries - Alma J. Adler; Laura Drown; Chantelle Boudreaux; Matthew M. Coates; Andrew Marx; Oyetayo Akala; Temo Waqanivalu; Hongyi Xu; Gene Bukhman (BMC, 2023)
Abstract Background Noncommunicable diseases (NCDs) and mental health conditions represent a growing proportion of disease burden in low- and middle-income countries (LMICs). While past efforts have identified interventions to be delivered across health system levels to address this burden, the challenge remains of how to deliver heterogenous interventions in resource-constrained settings. One possible solution is the Integration of interventions within existing care delivery models. This study reviews and summarizes published literature on models of integrated NCD and mental health care in LMICs. Methods We searched Pubmed, African Index Medicus and reference lists to conduct a scoping review of studies describing an integrated model of NCD or neuropsychiatric conditions (NPs) implemented in a LMIC. Conditions of interest were grouped into common and severe NCDs and NPs. We identified domains of interest and types of service integration, conducting a narrative synthesis of study types. Studies were screened and characteristics were extracted for all relevant studies. Results are reported using PRISMA-ScR. Results Our search yielded 5004 studies, we included 219 models of integration from 188 studies. Most studies were conducted in middle-income countries, with the majority in sub-Saharan Africa. Health services were offered across all health system levels, with most models implemented at health centers. Common NCDs (including type 2 diabetes and hypertension) were most frequently addressed by these models, followed by common NPs (including depression and anxiety). Conditions and/or services were often integrated into existing primary healthcare, HIV, maternal and child health programs. Services provided for conditions of interest varied and frequency of these services differed across health system levels. Many models demonstrated decentralization of services to lower health system levels, and task shifting to lower cadre providers. Conclusions While integrated service design is a promising method to achieve ambitious global goals, little is known about what works, when, and why. This review characterizing care integration programs is an initial step toward developing a structured study of care integration.